Anthropology of the gift of life - Pérez Soba Diez del Corral, Juan José (2019)
The moral value of life requires an adequate perspective, because in today's culture it tends to be perceived in relation to other realities, so it is reduced. This happens when it is measured from the reality of the cosmos as a part of it in a way that is almost insignificant, it is about cosmological reductionism. Also when human life is valued from the social appreciation that is pronounced from its functionality or efficiency, it is sociological reductionism. From these two visions it is affirmed that there are worthless lives that could be eliminated. Everything changes when we enter the logic of the gift, as the original light that sustains the meaning of life in the intentionality of the donor. We have to see human life as born of an original love and directed to love. It is the way to break the previous reductionisms and introduce a dialogic mode to discover the real meaning of human life. For the communicative good that contains the vital sense, its affirmation opens the way to a culture of life where the life of every man is valued and directed to conversion.